The effect of reduced graphene oxide addition on methane production from municipal organic solid waste - Gökçek, Öznur B.; Muratçobanoğlu, Fatma; Muratçobanoğlu, Hamdi; Uçar, Deniz; Mert, Ruhullah A. (John Wiley and Sons Ltd, 2021)
BACKGROUND: Conductive materials have become the focus of recent studies to accelerate and stabilize the conversion of organic wastes to methane in anaerobic digestion processes. In this study, the effect of the addition of reduced graphene oxide (rGO) on biogas/biomethane production from municipal organic solid wastes in anaerobic batch reactors was investigated. In this context, the effect of loading ratios (0, 0.5, 1 and 2 gVS inoculum (gVS nutrient)−1) and rGO addition at different concentrations (0, 10, 20 and 30 mg L−1) was examined during a 45-day study period. RESULTS: The highest biogas production reached a level of 816 ± 14 mL (gVS)−1 when substrate/inoculum ratio was 1 and 20 mg L−1 rGO was added (50% more than the group without rGO added). Addition of 30 mg L−1 rGO resulted in 667 ± 12 mL (gVS)−1 corresponding to 23% higher biogas production compared to the control reactor without rGO. The highest cumulative biomethane production was observed to be 525 ± 20 mL (gVS)−1 in the reactor with 20 mg L−1 rGO added in which substrate/inoculum ratio was 1. In the reactors with 10 and 30 mg L−1 and without rGO addition biomethane productions were 448 ± 21, 401 ± 13 and 323 ± 23 mL (gVS)−1, respectively. CONCLUSIONS: Results revealed that the addition of rGO increased biomethane production from municipal organic solid wastes. It is concluded that rGO addition has the potential to be applied for real-scale facilities within the scope of renewable energy production and circular economy. © 2021 Society of Chemical Industry.
Keywords: anaerobic digestion; biomethane; municipal organic solid waste; reduced graphene oxide